Storage and export of mercury from a contaminated bay (Ria de Aveiro, Portugal) - Ramalhosa, Elsa (2001)
Mercury has been determined in water, suspended particulate matter (SPM) and sediments (solid fraction and pore water) collected in a heavily contaminated confined area (Largo do Laranjo) of the Ria de Aveiro. Mercury has been analysed in seabass (Dicentrarchus labrax) captured in several locations of the lagoon. The levels of mercury in water and SPM in the contaminated sampled places fluctuated daily with the tide (from 10 to 53 ng.dm-3 and 3.5 to 26 ug.g-1, respectively), indicating the export at the tidal rhythm. Bottom sediments exhibited higher concentrations, the maximum (48 ug.g-1) occurring near the anthropogenic source at depths corresponding to the periods of higher industrial discharges. Mercury concentrations in pore waters (max. 80 ng.dm-3) exceed the values found in the water column and were higher at depths where Acid Volatile Sulphides (AVS) presented broad maximums. This implies a remobilization at anoxic conditions. However, the export across the sediment-water interface predicted through molecular diffusion is low (between 1 to 4 x 10-3 ng.cm-2.h-1) in comparison to the industrial input. The anthropogenic mercury appears to be rapidly accumulated in seabass, a predator fish that enter seasonally in Largo do Laranjo.